Innovative Pathways in English Curriculum Development - Yuniarti, Yuti (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The development of English language curricula is crucial for enhancing language proficiency and communication skills in an increasingly globalized world. However, despite advancements in educational theories, there remains a significant gap between the expected and actual practices in English language classrooms, particularly in the integration of innovative teaching methods. This study investigates innovative pathways in English curriculum development, focusing on bridging this gap by evaluating the effectiveness of contemporary approaches such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and the integration of digital tools. A mixed-methods approach was employed, involving questionnaires, surveys, and interviews with English teachers and students, alongside a review of curriculum documents. The findings revealed that while CLT and TBLT were perceived positively and had a significant impact on student engagement and speaking skills, methods like blended learning and flipped classrooms faced barriers such as a lack of resources and teacher readiness. The study concludes that integrating innovative methodologies into English curricula can enhance learning outcomes but requires systemic changes, including curriculum flexibility, teacher training, and better resource allocation. The implications suggest that educational institutions should prioritize professional development and infrastructure to support the effective integration of these innovative approaches into English language teaching.